Excitonic energy transfer in red algal Photosystem I reveals an evolutionary bridge between cyanobacteria and plants - Mengyuan Cui; Zihui Liu; Miriam Izzo; Junhua Zhou; Enhu He; Vandana Tiwari; Petar H. Lambrev; R. J. Dwayne Miller; Joanna Kargul; Fulu Zheng; Ajay Jha; Hong-Guang Duan (Proceedings of the National Academy of Sciences, 2026)
Photosystem I (PSI) converts light into chemical energy with near-unity quantum efficiency, yet its energy-transfer and charge-separation mechanisms remain debated. Evolution has diversified PSI architectures: Cyanobacterial PSI trimers confine red-shifted pigments to the core, whereas plant PSI-Light Harvesting Complex Isupercomplexes incorporate extensive peripheral red and charge-transfer states that reshape trapping. The unicellular red alga Cyanidioschyzon merolae exemplifies functional diversification across distinct evolutionary branches, combining a photosystem II and plant-like monomeric PSI core associated with a varying number of light harvesting antenna subunits, Light Harvesting Complexes from Red Lineage (LHCR). This hybrid organization functionally bridges mechanistic models across different lineages. We applied two-dimensional electronic spectroscopy at ultralow temperatures (8 and 80 K) to disentangle overlapping excitation pathways in C. merolae PSI. Cryogenic measurements suppressed thermal broadening, resolving five dynamical components: subpicosecond equilibration (0.3 to 0.8 ps) across the core–LHCR interface, subsequent population transfer (2.6 to 4 ps) into progressively lower-energy manifolds, and slower feeding (18 to 53 ps) into red pools distributed across both core and antenna. On the longest timescales (hundreds of ps), a persistent ground-state bleach signifies excitons stabilized in terminal sinks. Notably, comparison of 8 K and 80 K spectra reveals that excitations are heterogeneously partitioned among multiple sinks at low disorder, whereas modest thermal activation (kT ∼ 55 cm −1 ) promotes selective convergence into core-associated red chlorophylls. Atomistic excitonic modeling with time-nonlocal master equations supports these observations, revealing temperature-dependent energy redistribution. Overall, C. merolae PSI expands the kinetic funnel by distributing trapping sites, enhancing spectral coverage while maintaining high efficiency, which is an important functional diversification during evolution.